DANCE THERAPY: नृत्य चिकित्सा - Mandlik, Yogita (International Journal of Research -GRANTHAALAYAH, 2015)
Dance is the aesthetic language of organs and expressions. The dance expresses Karan, Angahar, Bhava, Vibhav, Anubhav and Rasas. Therefore, dance opens up a door to balanced delivery and development of organs and emotions, which gives satisfaction to the heart and mental conditions. The composition of Kathak dance makes the body a powerful powerful coordinated body and mental level and helps in providing spiritual peace at the spiritual level. Dance is a medium through which emotional energy is carried from one place to another. Dance therapy Kandabam Jimanchal is based on this. It can be called an experiment of speed that not only keeps us physically healthy, but also makes us mentally strong. Dance contains such elements by which the treatment of various diseases is possible. नृत्य अंगो व भावों की सौन्दर्यमयी भाषा हैं। नृत्य में करण, अंगहार, भाव, विभाव, अनुभाव और रसों की अभिव्यक्ति की जाती हैं। अतएव नृत्य द्वारा अंगो व भावों के संतुलित प्रसव और विकास का एक द्वार जैसा खुल जाता है, जो ह्दय और मानसिक स्थितियों को तृप्ति प्रदान करता है। कथक नृत्य की रचना देह को शारीरिक व मानसिक स्तर का समन्वित शक्तिशाली पुंज बना देती हैं और आध्यात्मिक स्तर पर आत्मिक शांति प्रदान करने में सहायक सिद्ध होती है। नृत्य एक ऐसा माध्यम है जिसके जरिए भावनात्मक ऊर्जा को एक जगह से दूसरी जगह ले जाया जाता हैं। नृत्य चिकित्सा क्ंदबम ज्ीमतंचल इसी पर आधारित है। इसे गति का एक ऐसा प्रयोग कह सकते है जो न सिर्फ हमंे शारीरिक रूप से स्वस्थ रहता है, बल्कि हमे मानसिक रूप से भी मजबुत बनाता है। नृत्य मंे ऐसे तत्व निहित होते है जिनके द्वारा विभिन्न रोगों की चिकित्सा संभव है।